2015
DOI: 10.1096/fj.15-272997
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of death effector domain chain assembly and its role in caspase‐8 activation

Abstract: Assembly of a death-inducing signaling complex is a key event in the extrinsic apoptotic pathway, enabling activation of the caspase cascade and subsequent cell death. However, the molecular events governing DISC assembly have remained largely elusive because of the lack of information on mechanism and specificity regulating the death effector domain (DED)-DED interaction network. Using molecular modeling, mutagenesis, and biochemical and ex vivo experiments, we identified the precise binding interface and hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…It has been previously demonstrated that the HPV18 E2 TAD binds directly to the tandem DED of procaspase-8 to induce apoptosis 13 . Since isolated procaspase-8 DEDs demonstrate strong tendency to aggregate and exhibit lack of solubility in buffers with different salt concentration and detergents 21 22 , we developed a bacterial co-expression system for interaction analyses. The individual genes, procaspase-8 tandem DEDs, DED-A, DED-B and E2 TAD, were sub-cloned in two compatible plasmid sets with different origin of replication, antibiotic selection, inducer and affinity-tag.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been previously demonstrated that the HPV18 E2 TAD binds directly to the tandem DED of procaspase-8 to induce apoptosis 13 . Since isolated procaspase-8 DEDs demonstrate strong tendency to aggregate and exhibit lack of solubility in buffers with different salt concentration and detergents 21 22 , we developed a bacterial co-expression system for interaction analyses. The individual genes, procaspase-8 tandem DEDs, DED-A, DED-B and E2 TAD, were sub-cloned in two compatible plasmid sets with different origin of replication, antibiotic selection, inducer and affinity-tag.…”
Section: Resultsmentioning
confidence: 99%
“…3A . Recently, we reported that two conserved hydrophobic patches ‘LXXϕ’ and ‘FL’-motifs on the opposite surfaces of DED-A and DED-B, respectively are essential for DED-AB self-association and DEF formation 22 . Importantly, the FL-motif on DED-B corresponds to residues F122/L123, the patch that we identified to be involved in E2-procaspase-8 interaction (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3d). Both DED1 and DED2 in the caspase-8 tandem DEDs have an FL motif; it has been established that the FL motif in DED2 is critical for dimerization, oligomerization, and the further activation of caspase-8, whereas the FL motif in DED1 is not associated with either oligomerization or caspase activation [72][73][74] . This result explains the reason that the FL motif in DED2 is critical for caspase-8 activation, showing that it is the primary mediator for caspase-8 domain swapping and dimerization (Fig.…”
Section: Domain-swapping-mediated Dimerization Of Dd Superfamily Membersmentioning
confidence: 99%